TINJAUAN KUAT TEKAN BETON GEOPOLYMER DENGAN FLY ASH SEBAGAI BAHAN PENGGANTI SEMEN - Prasetyo, Ginanjar Bagus; , Ir. H. Suhendro Trinugroho, MT; , Dr. Mochamad Solikin (2015)
Concrete is composed of coarse aggregate, fine aggregate, water, and Portland Cement (SP) is a material that is very important and widely used to build infrastructure. During the process of producing cement, the release of carbon dioxide (CO2) into the air in proportion to the amount of cement produced that can damage the environment or so-called greenhouse effect. In order to overcome these negative effects it is necessary to look for other materials as cement replacement materials. Geopolymer concrete is an alternative concrete created without the use of cement as a binder, and instead use fly ash that is rich in silica and alumina which can react with alkaline activator liquid to produce a binding agent (binder). Alkaline activator used in this study is Na2SiO3 (sodium silicate) and NaOH (sodium hydroxide) concentration of 10M. In this research, testing concrete compressive strength of the test specimen 15x15x15 cm3 cube with 45 specimen. Variation activator 1: 2, 2: 2, 3: 2, 4: 2 and 5: 2, while the use of aggregates and binders variation (fly ash and activator) is 75%: 25%, 70%: 30% and 65%: 35%. Curing is used by way of settling at room temperature. Tests carried out after the 28-day-old concrete. Based on the research results can be obtained graph of geopolymer concrete compressive strength of the comparison activator. For geopolymer concrete 75: 25, the highest compressive strength of concrete is owned by comparison Na2SiO3: NaOH = 5: 2 of 135.407 kg / cm2. For geopolymer concrete 70: 30, the highest compressive strength of concrete is owned by comparison Na2SiO3: NaOH = 5: 2 of 141.037 kg / cm2. And for geopolymer concrete 65: 35, the highest compressive strength of concrete is owned by a ratio Na2SiO3: NaOH = 4: 2 for 98.593 kg / cm2. The results showed that the higher the ratio of activator Na2SiO3: NaOH used in the concrete mix, then there is a tendency of increasing the compressive strength generated by each concrete.